Q: How do you solve 3(x 1) 2(x2 4x 5) 5(x 8)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2

(6-4x)(x-2)+3x =6x-12-4x+8x+3x =5x-4

4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3

5x + 3 = 4xSubtract 3 from each side:5x = 4x - 3Subtract 4x from each side:x = -3

Related questions

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

4x + -x = 3x

3x - 5x + 4x = -2x +4x = 2x

5x-2x-3x+4x = (5-2-3+4)x = 4x

2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2

5x-2 = 3x-6 5x = 3x - 6 +2 5x = 3x - 4 5x - 3x = -4 2x = -4 x = -2

If your equation is 5x-2=4x+4 Then this is how you solve it... 5x-2=4x+4 5x-2+2=4x+4+2 5x=4x+6 5x-4x=4x-4x+6 x=6 Your x=6

3x2 - 5x2 = -2x2

It is a mathematical equation, usually written like this: 5x - 7 + 2x = 3x - 2 + 4x

(6-4x)(x-2)+3x =6x-12-4x+8x+3x =5x-4

4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3

5x2 - 4x = 3x2 - 2xSubtract 3x2 from each side:2x2 - 4x = -2xAdd 2x to each side:2x2 - 2x = 0Divide each side by 2:x2 - x = 0Factor the left side:x(x - 1)=0x = 0andx = 1It took me almost 4 minutes, since I ran into some traffic.